The effect of ESG performance on firm value: financial performance as a mediating variable - Rayis, Dzulhijah Alkayyis; Juanda, Ahmad; Wicaksono, Agung Prasetyo Nugroho (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) performance on firm value, utilizing financial performance as a mediating variable. This study aims to fill a gap in the literature by examining the indirect effect of financial performance on the link between ESG and firm value, utilizing a sample of 24 non-financial businesses listed on the Indonesia Stock Exchange (IDX) from 2017 to 2024. A quantitative methodology was utilized, employing panel data regression analysis via the Fixed Effects Model (FEM) to examine the data, supplemented by tests for heteroskedasticity, endogeneity, and the Sobel and Hayes Model 4 to reinforce the findings. This study's innovation resides in employing financial performance as a mediator, offering fresh perspectives on how ESG activities might indirectly augment firm value via enhanced financial performance. The findings demonstrate that ESG performance significantly enhances firm value, but financial performance does not directly affect firm value in the majority of models. Financial performance serves a crucial mediating function in enhancing the connection between ESG performance and firm value. It is advised that organizations amalgamate sustainability initiatives with proficient financial management to augment long-term firm value. A subsequent study will investigate additional variables, including governance characteristics, and increase the sample size to corroborate these findings across diverse industries.